Assessment of Ti, Ir, Ta and Ru Influence on Mixed Metal Oxide Electrodes for Photoelectrochemical Generation of Persulfate: Impact on Sulfamethoxazole Degradation - Salazar-Gonzalez, R (Elsevier Ltd, 2024)
The presence of persulfate (S2O82−) in decontamination processes favors the oxidation of organic pollutants due to its strong oxidation power. In this research we study the photoelectrochemical generation of persulfate using five mixed metal oxides electrodes (MMO) with different compositions and its effect on the degradation of sulfamethoxazole antibiotic (SMX) by photoelectrocatalysis (PEC) and electro-oxidation (EO). By PEC, all anodes generated a higher concentration of S2O82− than those not exposed to light. The high S2O82−concentration obtained by PEC was 0.150 mM using MMO[Ti/Ir/Ta] in a solution with Na2SO4 100 mM applying a current density of 2 mA/cm2. On the other hand, the maximum concentration obtained was 0.250 mM at 30 min of electrolysis for MMO[Ti/Ir/Ta] using Na2SO4 50 mM and applying current density of 5 mA/cm2. S2O82−production by EO was between 0.005 and 0.089 mM. It is observed that MMO based in Ta2O5 showed the best S2O82− production. The effect of S2O82− electro-generation (using the anode with the highest and the anode with the lowest S2O82− production) on the degradation of sulfamethoxazole by PEC and EO was studied using the experimental conditions with the best production of this oxidant. MMO[Ti/Ir/Ta] and MMO[Ti/Ru] were used as anodes, and it was observed that by PEC, 100% of SMX was degraded after 30 min of electrolysis using MMO[Ti/Ir/Ta] and 60 min using MMO[Ti/Ru]. By EO, the degradation of SMX was partial, demonstrating that the electrophotocatalytic effect favors the generation of S2O82−, enhancing the degradation of SMX at short electrolysis times. © Elsevier Ltd